Production, Purification, and Properties of a Thermostable β-Glucosidase from a Color Variant Strain of Aureobasidium pullulans - Saha, Badal C. (1994)
A color variant strain of Aureobasidium pullulans (NRRL Y-12974) produced β-glucosidase activity when grown in liquid culture on a variety of carbon sources, such as cellobiose, xylose, arabinose, lactose, sucrose, maltose, glucose, xylitol, xylan, cellulose, starch, and pullulan. An extracellular β-glucosidase was purified 129-fold to homogeneity from the cell-free culture broth of the organism grown on corn bran. The purification protocol included ammonium sulfate treatment, CM Bio-Gel A agarose column chromatography, and gel filtrations on Bio-Gel A-0.5m and Sephacryl S-200. The β-glucosidase was a glycoprotein with native molecular weight of 340,000 and was composed of two subunits with molecular weights of about 165,000. The enzyme displayed optimal activity at 75°C and pH 4.5 and had a specific activity of 315 μmol · min(-1) · mg of protein(-1) under these conditions. The purified β-glucosidase was active against p-nitrophenyl-β-d-glucoside, cellobiose, cellotriose, cellotetraose, cellopentaose, cellohexaose, and celloheptaose, with K(m) values of 1.17, 1.00, 0.34, 0.36, 0.64, 0.68, and 1.65 mM, respectively. The enzyme activity was competitively inhibited by glucose (K(i) = 5.65 mM), while fructose, arabinose, galactose, mannose, and xylose (each at 56 mM) and sucrose and lactose (each at 29 mM) were not inhibitory. The enzyme did not require a metal ion for activity, and its activity was not affected by p-chloromercuribenzoate (0.2 mM), EDTA (10 mM), or dithiothreitol (10 mM). Ethanol (7.5%, vol/vol) stimulated the initial enzyme activity by 15%. Glucose production was enhanced by 7.9% when microcrystalline cellulose (2%, wt/vol) was treated for 48 h with a commercial cellulase preparation (5 U/ml) that was supplemented with the purified β-glucosidase (0.21 U/ml) from A. pullulans.